Salt glands in the Poaceae Family and their relationship to salinity tolerance - Céccoli, Gabriel; Ramos, Julio Cesar; Pilatti, Vanesa; Dellaferrera, Ignacio Miguel; Tivano, Juan; Taleisnik, Edith; Vegetti, Abelardo Carlos (Springer, 2018)
The Poaceae is one of the most important Angiosperm families, in terms of morphological diversity, ecology and economic importance. Species within this family show a very wide variation in terms of salinity tolerance. Salt secretion through salt glands plays a significant role in regulating ion balance, contributing to salinity tolerance. This review focuses on salt glands in the Poaceae family and their role in the salinity tolerance. In Poaceae microhairs have been observed in all subfamilies, except Pooideae, but functioning salt glands are reported only in genera belonging to the Chloridoideae subfamily. Structural, ultrastructural and physiological features of salt glands are summarized and discussed and the use of salt glands as potential target features for improving salt tolerance of crops is considered.